If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 268 * 12 = x Multiply 268 * 12 3216 = x Solving 3216 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3216 + -1x = x + -1x Combine like terms: x + -1x = 0 3216 + -1x = 0 Add '-3216' to each side of the equation. 3216 + -3216 + -1x = 0 + -3216 Combine like terms: 3216 + -3216 = 0 0 + -1x = 0 + -3216 -1x = 0 + -3216 Combine like terms: 0 + -3216 = -3216 -1x = -3216 Divide each side by '-1'. x = 3216 Simplifying x = 3216
| 145.50p+2250=4432.50 | | 3r+4=12r+1 | | 268*8=x | | x^4-16x^3+48x^2-16x+288=0 | | 10-2(4x+9)=20+12x | | 268*30=x | | 9x-4=-6 | | -12y=2y+40 | | 2j-12=-15 | | 8y-6-3y+3=0 | | 4k-5(k-8)=2(k+2) | | 5x+10(52-x)=450 | | 63=5v-12 | | 3(x+1)-2(3x-7)=14 | | 25x^2+x-3=0 | | x^2-6x=-2x+60 | | x-2=144 | | 5(2x-3)=14 | | y-18+5x=0 | | 12-3x=22+5x | | 108=72-180 | | 2m-3m-8n+n= | | 5(y+7)+-2(3+y)= | | 13y-9y-10=53.48 | | (3x+8)+(3x+7)+(3x)=(3x)+(3x)+(4x+5) | | 5x-3+2x+1=8+3x+2 | | 27=3z-5z+9+4z | | -7(3y+2)=8(3y-2) | | 6x+3[2y-x]= | | -2x-39=59-9x | | -9.39+-3.4d=-1.1d+11.08 | | b+3-6b=-3+b |